Mechanical properties of dense cordierite discs sintered by solar radiation heating - Oliveira, Fernando Almeida Costa (2010)
Consolidation of cordierite disc specimens was undertaken under concentrated solar beam in a solar furnace at PSA (Plataforma Solar de Almerıá). Satisfactory extent of densification was achieved by the present solar-sintering experiment. The mechanical properties measured for the solar-sintered cordierite test pieces were; density ¼ 2:45 0:02 g/cm3, Vickers microhardness HV ¼ 7:31 0:29 GPa, Young’s modulus E ¼ 97 5 GPa, shear modulus G ¼ 38 2 GPa, Poisson ratio ¼ 0:27 0:01, fracture toughness KIC ¼ 1:50 0:15 MPa m1=2 and modulus of rupture evaluated by ring-on-ring test MORROR ¼ 57:8 13:7 MPa which were comparable to those of the counterparts sintered by conventional industrial gas furnace.